Behavioral sensitization to different dopamine agonists in a parkinsonian rodent model of drug-induced dyskinesias - Delfino, M.A. (2004)
Repeated treatment with dopamine (DA) receptor agonists strongly potentiates contralateral turning behavior due to selective stimulation of D1 or D2-class receptors in 6-hydroxydopamine (6-OHDA)-lesioned rats. This phenomenon, referred to as sensitization, is believed to be related to the motor response complications (dyskinesias, on-off states) that occur during chronic administration of levodopa in Parkinson’s disease patients. In recent years a new method for the evaluation of abnormal involuntary movements (AIMs) secondary to dopaminergic stimulation in 6-OHDA-lesioned rats was described. These AIMs resemble dyskinesias as seen in parkinsonian patients under levodopa therapy. Our objective was to evaluate the effects of repeated treatment with different regimes of DA agonists on turning behavior and on an AIMs scale in 6-OHDA lesioned rats, with the aim of discriminating between drugs with different dyskinesia-inducing potential. In addition, we explored the effects of a previous exposure to a DA agonist (priming) on the behavioral response to the subsequent administration of a DA agonist with the same or different pharmacologic profile. Our results show that in apomorphine-treated rats, rotational behavior and AIMs run a parallel course of enhancement, while in those receiving quinpirole there is a dissociation, suggesting that they could be mediated by different mechanisms. The finding of a significant priming effect on subsequent testing of 6-OHDA lesioned rats should be borne in mind as the use of these pharmacological tests in the screening of well lesioned animals could lead to an erroneous interpretation of further results on dyskinesias and rotational behavior.